STUDENT’S ANALYSYS OF PERCEPTION TEACHERS BILINGUAL LANGUAGE USE IN SPEAKING CLASSROOM AT MTs AL -AMIN MALANG - Elta Rizma Ifari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstarct: In the teaching and learning process, communication has become one of the key primaries between the recipient and the informer. This research used a qualitative data approach. The sample consisted of 30 students in the eighth grade that separated A and B class at MTs Al-Amin Malang. The data was collected by using a questionnaire and interview. The findings of this research is this study proves that students' positive perceptions of using bilingual-based materials as language teaching in English classes. The amount of this statement reached a percentage of 86.6% of students. The most answer is "Yes" because they feel that the bilingual language teachers use to make them know the explanation easier. In addition, it can be concluded that student perception in teacher using bilingual language in speaking classroom at MTs Al-Amin Malang based on questionnaire and interview data are showing a positive response. The researcher suggests that the next research on finding must be more get the valid data and will use the newest parameters found by other researcher other than those who have mention above.